2009
DOI: 10.1088/0031-8949/80/01/015501
|View full text |Cite
|
Sign up to set email alerts
|

Ion acoustic shock waves in dissipative electron–positron–ion plasmas with weak transverse perturbations

Abstract: Ion acoustic shock waves (IASWs) are studied in an unmagnetized plasma consisting of electrons, positrons and adiabatically hot positive ions. This is done by deriving the Kadomstev-Petviashvilli-Burger (KPB) equation under the small-amplitude perturbation expansion method. The dissipation is introduced by taking into account the kinematic viscosity among the plasma constituents. The dependence of the IASWs on various plasma parameters is explored in detail. It is observed that an increasing positron concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 26 publications
4
8
0
Order By: Relevance
“…It is clear that at higher positron concentration, the driving force of the wave diminishes and consequently the shock declines. This is consistent with the result in Shah andSaeed (2009) andMasood et al (2009) for relativistic and nonrelativistic e-p-i plasma with the kinematic viscosity among the plasma constituents. It is also obvious that the amplitude increases with increasing values of spectral index k. This result consistent with the one made by Boubakour et al (2009) for ion acoustic solitary waves in e-p-i plasma with superthermal electrons.…”
Section: Derivation Of Kdv Burger Equation and Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It is clear that at higher positron concentration, the driving force of the wave diminishes and consequently the shock declines. This is consistent with the result in Shah andSaeed (2009) andMasood et al (2009) for relativistic and nonrelativistic e-p-i plasma with the kinematic viscosity among the plasma constituents. It is also obvious that the amplitude increases with increasing values of spectral index k. This result consistent with the one made by Boubakour et al (2009) for ion acoustic solitary waves in e-p-i plasma with superthermal electrons.…”
Section: Derivation Of Kdv Burger Equation and Discussionsupporting
confidence: 92%
“…It is found that an increase in η 0 (meaning an increase in dissipation) considerably enhances the amplitude as well as the steepness of the shock front. This result congruent with the one made by Masood et al (2009) in ep-i plasma consisting adiabatically hot positive ions and by Masood et al (2008b) in quantum e-p-i plasma. This result also is in agreement with the result of Shah and Saeed (2009) for e-p-i plasma with the Boltzmann distribution of electron.…”
Section: Derivation Of Kdv Burger Equation and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It is found that an increasing in η • (meaning an increasing in dissipation) considerably enhances the amplitude as well as the steepness of the shock front. This result congruent with the one made by Masood et al (2009) in e-p-i plasma consisting adiabatically hot positive ions and by Masood et al (2008) in quantum e-p-i plasmas. This result also is in agreement with the result of Shah et al (2009) for e-p-i plasma with the Boltzmann distribution of electron.…”
Section: Derivation Of Kdv Burger Equation and Discussionsupporting
confidence: 87%
“…As a consequence, a high-energy tail appears in the distribution function of the particles. Only few investigations have been reported on the study of ion acoustic shock waves in relativistic plasmas (Shah and Saeed 2009;Masood et al 2008;Masood et al 2009). The aim of the present paper is study of ion-acoustic shock waves in plasmas consisting of relativistic ions, Maxwell-Boltzmann distributed positrons and nonthermal electrons.…”
Section: Introductionmentioning
confidence: 99%